2014
DOI: 10.1002/bdra.23278
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous FGF8 mutations in patients presenting cryptorchidism and multiple VATER/VACTERL features without limb anomalies

Abstract: Our results suggest FGF8 mutations to contribute to the formation of the VATER/VACTERL association. Further studies are needed to support this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…A recent FGF8 analysis by Zeidler and colleagues [58] in 78 patients with VATER/VACTERL association or VATER/VACTERL-like phenotype revealed two different mutations. While the p.Gly29_Arg34dup mutation in a patient with five CFs (‘ACTERL’) including horseshoe kidney has not been reported yet, the p.Pro26Leu substitution in a patient with two CFs (‘AR’), comprising right-sided renal dysplasia, had earlier been found in a patient with Kallmann syndrome (KS) who did not show any CFs of the VATER/VACTERL association [59].…”
Section: Human Disease Genes In Patients With Vater/vacterl-like Phenmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent FGF8 analysis by Zeidler and colleagues [58] in 78 patients with VATER/VACTERL association or VATER/VACTERL-like phenotype revealed two different mutations. While the p.Gly29_Arg34dup mutation in a patient with five CFs (‘ACTERL’) including horseshoe kidney has not been reported yet, the p.Pro26Leu substitution in a patient with two CFs (‘AR’), comprising right-sided renal dysplasia, had earlier been found in a patient with Kallmann syndrome (KS) who did not show any CFs of the VATER/VACTERL association [59].…”
Section: Human Disease Genes In Patients With Vater/vacterl-like Phenmentioning
confidence: 99%
“…However, besides delayed puberty in both and unilateral cryptorchidism in one of the fathers, they were otherwise healthy. This suggests a variable expressivity for mutations in FGF8 in which patients with VATER/VACTERL association may constitute the severe end [58]. According to MGD Fgf8 tm1.3Mrt / Fgf8 tm1.4Mrt mice display abnormal kidney development and absent renal glomerulus [56].…”
Section: Human Disease Genes In Patients With Vater/vacterl-like Phenmentioning
confidence: 99%
“…Otherwise, it has been shown that some signaling pathways, such as sonic hedgehog, Hox and retinoic acid pathways could also be implicated in the etiology [Solomon, 2011;Brosens et al, 2014]. Individuals with VAC-TERL features were identified with mutations of ZIC3 and FOXF1 [Chung et al, 2011;Hilger et al, 2015], FGF8 [Zeidler et al, 2014], PTEN [Reutter and Ludwig, 2013], and HOXD13 [Garcia-Barcelo et al, 2008]. A study of 69 twins affected by VACTERL association did not show a higher concordance rate in monozygotic twins than in dizygotic twins, and therefore suggested that inherited genetic factors play a limited role in this condition [Bartels et al, 2012b].…”
Section: Vacterl Associationmentioning
confidence: 99%
“…Furthermore, in 66% of naturally cryptorchid mice, treatment with LH-releasing hormone reportedly induces epididymo-testicular descent, while increasing testosterone secretion and normalizing morphology of the underdeveloped cryptorchid epididymis [Hadziselimovic, 1981]. Notably, FGF8 mutation contributes to formation of the VATER/VACTERL association and is involved in cryptorchidism development [Zeidler et al, 2014].…”
Section: Role Of Gonadotropin-releasing Hormone and Fgfsmentioning
confidence: 99%